Effect of Trichoderma spp. and Purpureocillium lilacinum on Meloidogyne javanica in commercial pineapple production in Kenya - Kiriga, A.W.; Haukeland, Solveig; Kariuki, G.M.; Coyne, Danny L.; Beek, N.V. (Elsevier, 2018)
Plant-parasitic nematodes, in particular Meloidogyne species, cause significant yield reduction in commercial pineapple, Ananas comosus, worldwide. The efficacy of three Trichoderma isolates (Trichoderma asperellum M2RT4, T. atroviride F5S21, Trichoderma sp. MK4) and two isolates of Purpureocillium lilacinum (KLF2 and MR2) were evaluated against Meloidogyne javanica, using rooted pineapple crowns in a pot experiment under greenhouse conditions. All the three Trichoderma isolates successfully colonized pineapple root endophytically. The application of two isolates of Trichoderma (T. asperellum M2RT4 and Trichoderma sp. MK4) and the two isolates of P. lilacinum significantly reduced nematode egg and egg mass production reducing root galling damage by between 60.8 and 81.8% and increased the plant root mass growth compared to the untreated control. T. asperellum M2RT4 most effectively reduced galls, egg mass and eggs, by 81.8, 78.5 and 88.4% respectively. P. lilacinum MR2 most effectively reduced galls, egg mass and eggs, by 71.6, 73.9 and 82.6% respectively. In contrast Trichoderma atroviride F5S21 application had no significant effect on nematode multiplication or root damage compared with the control. Inoculation with T. asperellum M2RT4 increased root fresh weight by 91.5%, Trichoderma sp. MK4 by 63.8%, T. atroviride F5S21 by 50.0%, P. lilacinum KLF2 by 43.8% and MR2 by 32.3%. Results indicate that local isolates Trichoderma spp. and P. lilacinum directly and indirectly affected nematode reproduction and host response, demonstrating their control potential against M. javanica on pineapple. Such alternative options for managing Meloidogyne spp. would provide more environmentally sensitive options for combining with other management methods towards more sustainable pineapple production systems.